Analisis kontribusi konsep matematis pada sawah lodok khas kearifan lokal masyarakat manggarai - Lana Sugiarti; Ali, Ferdinandus Ardian (IKIP Siliwangi, 2023)
This study aims to find out the contribution of mathematical concepts to lodok rice fields (ricefield spider net) in Manggarai Regency. The main instrument is the researcher himself, and the supporting instruments are observation and interview guidelines. Data was collected by means of field observations and interviews with manggarai traditional leaders, where the selection of traditional leaders used a purposive sampling technique. To obtain valid and reliable data, the researchers used technique triangulation and source triangulation. Data analysis used is reducing data, presenting data, and drawing conclusions or verification. The results of the study found that the shape of lodok rice fields in Manggarai Regency was made by applying the concept of ''Circle Center Point'' at the meeting point (node point) of the land of all residents, which is referred to as Lodok and the concept of ''Juring Circle'' on the shape and size of the land area of each resident as well as a barrier to land ownership rights between one resident and another, known as Langang or Lance.